2021
DOI: 10.1038/s41598-021-82535-3
|View full text |Cite
|
Sign up to set email alerts
|

Resolving whether inhalation of depleted uranium contributed to Gulf War Illness using high-sensitivity mass spectrometry

Abstract: Of the hypothesized causes of Gulf War Illness (GWI), a chronic multi-symptom illness afflicting approximately 25% of military personnel deployed to the 1991 Gulf War, exposure to depleted uranium (DU) munitions has attracted international concern. Past research has not tested the potential association of GWI with inhaled DU nor used isotope mass spectrometry of sufficient sensitivity to rigorously assess prior DU exposure. We applied a standard biokinetic model to predict the urinary concentration and uranium… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In a recent study, samples from 154 U.S. veterans were tested for urinary depleted uranium [ 91 ]. The results found no differences in 238 U/ 235 U ratios, no differences in depleted uranium inhalation exposure levels, and no detectable 236 U associated with depleted uranium.…”
Section: Inhalation Damage Of Particulate Uraniummentioning
confidence: 99%
“…In a recent study, samples from 154 U.S. veterans were tested for urinary depleted uranium [ 91 ]. The results found no differences in 238 U/ 235 U ratios, no differences in depleted uranium inhalation exposure levels, and no detectable 236 U associated with depleted uranium.…”
Section: Inhalation Damage Of Particulate Uraniummentioning
confidence: 99%
“…The commonly reported symptoms include neurologic problems such as concentration difficulties, mood alterations (e.g., anxiety and depressive symptoms), and memory dysfunctions (Committeeon Gulf War and Health, 2016). Although many deployment-related factors have been studied for GWI development ( Steele et al, 2012 ; White et al, 2016 ), several lines of research now convincingly point toward the involvement of the organophosphate (OP) category of compounds in GWI etiology ( Haley and Tuite, 2013 ; Tuite and Haley, 2013 ; Parrish and Haley, 2021 ; Haley et al, 2022 ). OPs include pesticides and chemical-warfare agent sarin ( Costa, 2018 ), and there is evidence that Gulf War (GW) soldiers were exposed to these compounds during deployment ( Ribeiro and Deshpande, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…U.S. and British forces used depleted uranium in armor-piercing rounds to disable enemy tanks during the Gulf and Balkan Wars, which led to speculations on possible associations between exposure to depleted uranium and adverse health outcomes among veterans and civilians (Marshall 2007 ; Shaki et al 2019 ; Surdyk et al 2021 ). A recent investigation of Parrish and Haley ( 2021 ) has resolved this question. The authors used a bio-kinetic model to predict the urinary concentration and uranium isotopic ratios for a range of inhalation exposures.…”
mentioning
confidence: 99%
“…No difference was found in the 238 U/ 235 U ratio in veterans meeting the standard case definitions of Gulf War Illness versus control veterans, no differences by levels of depleted uranium inhalation exposure, and no 236 U, associated with depleted uranium, was detected. These findings showed that even the highest likely levels of depleted uranium inhalation played no role in the development of Gulf War Illness, leaving exposure to aerosolized organophosphate compounds (pesticides and sarin nerve agent) as the more likely cause(s) of Gulf War Illness (Parrish and Haley 2021 ).…”
mentioning
confidence: 99%